Projeto de Integração do rio São Francisco – PISF: recortes da injustiça hídrica no semiárido paraibano - Silva, Maicon Miguel Vieira da (2022)
The present research was developed within the scope of the Graduate Program in Agroecology and Development at the Federal University of São Carlos - SP. Its objective was to characterize processes of water (In)justice suffered by rural communities in the Brazilian Semi-Arid region from the implementation of the Project for the Integration of Hydrographic Basins of the Northern Northeast (PISF). The research was developed in four stages, the first refers to a re-reading of quantitative data produced by the author of this research, for the development of his monograph, but which presents relevant information for the debate on Water (In)justice. The second stage consisted of a literature review on Water (In)justice. The debate was systematized and presented in the second section of this work. The third step is to carry out a field interview in the territories Vila Produtiva Rural Lafayette and Pau D'arco/Mulungu, located in the rural area of the municipality of Monteiro-PB. The field research consists of carrying out a qualitative interview to identify the possible water (In)justices present in the researched communities, considering the analytical dimensions that deal with accumulation, conflicts and actions of civil society, present in the theoretical framework. The fourth and last stage is presented in the systematization of field data. The processes related to ACCUMULATION were categorized into “Commitments of water sources”, “Concentration of water sources” and “Water commodification”; processes related to CONFLICTS were categorized into “Community Conflicts”, “Inter-Community Conflicts”, “Community vs State Conflicts” and finally “Community vs Ministry Conflicts”; processes related to civil society action were categorized into “Formations and partnerships”, “Struggles and social mobilizations” and “Projects” according to the discussions presented in section three of this work. The conclusions indicate that the water (In)justices are characterized in several fields, more in particular with regard to the conditions of access, quality, and commercialization of water, as well as in the conflicts generated by the PISF in a direct and indirect way. In order to combat injustices, the resistance of the victimized communities is attested through the actions of civil society, which has done a lot to repair the impacts caused by water injustices, which the territories were subordinated to.